Glioblastoma 2017
DOI: 10.15586/codon.glioblastoma.2017.ch13
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Mapping in the Resection of Malignant Cerebral Gliomas

Abstract: Cerebral gliomas are diffuse intrinsic primary brain tumors that are most commonly encountered in the frontal, temporal, and parietal lobes, and that can present with an array of symptoms including alterations in mental status, speech and language difficulties, motor or sensory abnormalities, and seizures. Maximal safe surgical debulking of the tumor reduces mass effect, provides a precise histological diagnosis, and facilitates genetic analysis that may shed light on the response to therapies and prognosis, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…In our study, we noticed that surgery was performed to excise metastases located especially in functionally important areas, such as “eloquent brain areas”, which are nervous regions that in case of an injury can result in loss of function [ 12 ], or in cerebellum, which is a major motor structure [ 13 ].…”
Section: ⧉ Discussionmentioning
confidence: 99%
“…In our study, we noticed that surgery was performed to excise metastases located especially in functionally important areas, such as “eloquent brain areas”, which are nervous regions that in case of an injury can result in loss of function [ 12 ], or in cerebellum, which is a major motor structure [ 13 ].…”
Section: ⧉ Discussionmentioning
confidence: 99%
“…Consistent with this study, her language functions also completely recovered as observed during the 6-month follow-up. Damage to motor/sensory areas and arcuate fasciculus between anterior and posterior language areas possibly result in permanent language deficits with respect to speech comprehension or production ( 6 , 9 ). This patient fortunately did not have epileptic foci in these regions.…”
Section: Discussionmentioning
confidence: 99%
“…Anterior (Broca’s) and posterior (Wernicke’s) language areas are classical representatives of language areas. Anterior language area was considered to be associated with expressive language function and distribute across Brodmann’s areas 44 and 45, while posterior language area was considered to be associated with comprehension and understanding language, and correspond to Brodmann’s areas 22 and 39 ( 6 8 ). Recent studies on the associations between cerebral injuries and language functions revealed that the language areas generally extend to middle frontal gyrus, sensorimotor area, posterior temporoparietal area, anterior and posterior temporal areas, and the sites other than cortices, including the basal ganglia, arcuate fasciculus, and superior longitudinal fasciculus and that these areas are associated with impairments in speech comprehension and production ( 6 , 8 , 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is necessary to define the extent of resection to balance maximizing the resected volume and minimizing damage or injury to eloquent or association cortices alongside the resection boundary. [2].…”
Section: Introductionmentioning
confidence: 99%